ENHANCEMENT OF COMMUNICATION ABILITIES IN ELEMENTARY SCHOOL STUDENTS (Web of Teachers: Inderscience Research, 2024)
The article analyzes the peculiarities of developing communicative competence in elementary school students through educational games. It examines the initial level of communication skills and abilities in schoolchildren through experimental research. The article also distinguishes between the concepts of "communicative competence" and "language competence." The analysis highlights the main methods for integrating games into the educational process to foster communicative competence in elementary school students. The impact of educational games on the development of communicative competence is discussed, noting that it involves more than just acquiring language and speech knowledge. It also encompasses the practical use of language in communication, including the ability to choose appropriate communication strategies and apply relevant skills. The process of forming communicative competence in elementary school students includes developing verbal and nonverbal communication skills, enhancing both dialogue and monologue speech, mastering oral and written language culture, and acquiring the ability to navigate various communicative situations.